2012
DOI: 10.1167/tvst.1.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Ensheathing Cells Rescue Optic Nerve Fibers in a Rat Glaucoma Model

Abstract: Purpose: To determine if transplantation of olfactory ensheathing cells (OECs) can reduce loss of optic nerve axons after raised intraocular pressure (IOP) in the rat.Methods: OECs cultured from the adult olfactory mucosa were transplanted into the region of the optic disc. The IOP was raised by injection of magnetic microspheres into the anterior chamber.Results: At 4 weeks after raising the IOP, the transplanted OECs had migrated into the dorsal area of the optic nerve head (ONH) where they surrounded the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(22 citation statements)
references
References 39 publications
0
21
1
Order By: Relevance
“…The means ± SEM of four consecutive readings of IOP were 10.0 ± 0.75 mm Hg ( n = 28) before injection, 17.7 ± 0.80 ( n = 6) at 4 days, 20.1 ± 1.29 ( n = 8) at 7 days, 24.3 ± 3.71 ( n = 8) at 14 days, and 13.4 ± 1.14 ( n = 6) at 28 days. In the present series of rats the IOP measurements under combined general and local anaesthesia were considerably lower than in the previous series (Dai et al, ) where only local anaesthesia was used.…”
Section: Methodscontrasting
confidence: 80%
See 1 more Smart Citation
“…The means ± SEM of four consecutive readings of IOP were 10.0 ± 0.75 mm Hg ( n = 28) before injection, 17.7 ± 0.80 ( n = 6) at 4 days, 20.1 ± 1.29 ( n = 8) at 7 days, 24.3 ± 3.71 ( n = 8) at 14 days, and 13.4 ± 1.14 ( n = 6) at 28 days. In the present series of rats the IOP measurements under combined general and local anaesthesia were considerably lower than in the previous series (Dai et al, ) where only local anaesthesia was used.…”
Section: Methodscontrasting
confidence: 80%
“…We recently presented evidence that transplanted OECs are able to ensheath RGC axons, induce angiogenesis and reduce the degradation of the FAST array caused by raised IOP (Dai et al, ). We suggest that the ensheathment of the axons may preserve their vital energy input, and that the angiogenesis induced by the transplants may restore the blood supply to the remaining FASTs (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Samsel et al proposed a novel “Bead Model” in which magnetic particles could cause highly elevated IOP values and showed that this resulted in severe axon damage within 4 weeks. The short duration and severe damage evoked by this model can be classified as acute neuropathy and not chronic glaucomatous damage, although IOP elevation is the basic mechanism through which the nerves are injured252627.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous studies we have demonstrated that transplantation of cultured olfactory mucosal cells (OMCs) consisting mainly of OECs and ONFs before raising the IOP in a rat model could reduce the damage to ONH astrocytes and moderate the loss of optic nerve axons (Dai et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%